Exogenous application of ZnO nanoparticles and ZnSO4 distinctly influence the metabolic response in Phaseolus vulgaris L - Salehi, Hajar; De Diego, Nuria; Chehregani Rad, Abdolkarim; Benjamin, Jenifer Joseph; Trevisan, Marco; Lucini, Luigi (The Science of the total environment, 2021)
Nanomaterials-mediated contamination (including the highly reactive metal oxides ZnO nanoparticles) is becoming one of the most concerning issues worldwide. In this study, the toxic effects of two chemical species of Zn (ZnO nanoparticles and bulk ZnSO4) were investigated in bean plants, following either foliar or soil application, at concentrations from 250 to 2000 mg L-1 using biochemical assays, proteomics and metabolomics. The accumulation of Zn in plant tissues depended on the application type, zinc chemical form and concentration, in turn triggering distinctive morphological, physiological, and redox responses. Bean plants were more sensitive to the foliar than to the soil application, and high concentrations of ZnO NP and bulk ZnSO4 determined the highest plant growth inhibition and stress symptoms. However, low dosages of ZnSO4 induced a slight plant growth promotion and better physiological and antioxidative response. Low concentration of Zn leaded to increased activity of stress-related proteins and secondary metabolites with antioxidant capacity, while increasing concentration reached the exhausted phase of the plant stress response, reducing the antioxidant defense system. Such high concentrations increased lipids peroxidation, protein degradation and membranes integrity. Oxidative damage occurred at high concentrations of both chemical species of Zn. Foliar spraying impaired photosynthetic efficiency, while soil applications (especially ZnSO4) elicited antioxidant metabolites and proteins, and impaired chloroplast-related proteins involved in the electron transport chain and ATP production. Taken together, the results highlighted distinctive and nanoparticles-related toxic effects of ZnO in bean, compared to ionic forms of Zn.
Keywords: Photosynthesis; oxid zinečnatý; Phaseolus; Secondary metabolism; Nanoparticles; fazol; Zinc Oxide; půda; Soil; Plant stress; Zinc; fotosyntéza; Omics analysis; zinek; Oxidative stress; nanočástice